Health care managers learning by listening to subordinates' dialogue training. Issue 3 (10th June 2014) - Grill, C.; Ahlborg Jr, G.; Wikström, E.
Abstract : Purpose: – Middle managers in health care today are expected to continuously and efficiently decide and act in administration, finance, care quality, and work environment, and strategic communication has become paramount. Since dialogical communication is considered to promote a healthy work environment, the purpose of this paper is to investigate the ways in which health care managers experienced observing subordinates' dialogue training. Design/methodology/approach: – A qualitative study using semi-structured interviews and documents from eight middle managers in a dialogue programme intervention conducted by dialogue trainers. Focus was on fostering and assisting workplace dialogue. Conventional qualitative content analysis was used. Findings: – Managers' experiences were both enriching and demanding, and consisted of becoming aware of communication, meaning perceiving interaction between subordinates as well as own silent interaction with subordinates and trainer; Discovering communicative actions for leadership, by gaining self-knowledge and recognizing relational leadership models from trainers – such as acting democratically and pedagogically – and converting theory into practice, signifying practising dialogue-promoting conversation behaviour with subordinates, peers, and superiors. Research limitations/implications: – Only eight managers participated in the intervention, but data afforded a basis for further research. Practical implications: – Findings stressed the importance of listening, and of support from superiors, for well-functioning leadership communication at work. Originality/value: – Studies focusing on health care managers' communication and dialogue are few. This study contributes to knowledge about these activities in managerial leadership.